UNIVERSITY UNDERGRADUATE STUDENTS’ ASSESSMENT OF THE APPLICATION OF INFORMATION TECHNOLOGY TO PHYSICS EDUCATION - Esther, Omosewo (European Scientific Journal, ESJ, 2012)
In this paper, university undergraduate students’ assessment of the application of information technology to physics education was looked into. Eighty five final year educational technology students of the University of Ilorin who minored in introductory technology (physics component) participated in the study. Three research questions were generated and they were answered using frequency counts and percentage. A researcher- designed structured questionnaire was used to gather necessary data. The findings from the study revealed that sampled students opined that: relevant textbooks should be made available to students, computer graphics and projected media to be used by physics teachers, and they also noted that chalkboard and visuals can be used for effective teaching of physics concepts. Appropriate recommendations were made by the researcher.